Comparison of Amsel’s criteria and Nugent’s criteria for diagnosis of bacterial vaginosis in tertiary care centre - Bansal, Romi; Garg, Priyanka; Garg, Aastha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Bacterial vaginosis is an imbalance in the ecology of the normal vaginal flora which is characterized by depletion of lactobacilli, and proliferation of anaerobic bacteria. It most often manifests clinically as a vaginal pH of > 4.5, presence of thin whitish homogenous vaginal discharge, detection of “clue” cells and presence of an amine odour after the addition of 10 percent potassium hydroxide. These anaerobic bacteria through specific products stimulate the decidual tissue causing an increase of cytokine level, release of phospholipase A2 and prostaglandins leading to preterm labor, premature rupture of membranes, chorioamnionitis and development of PID following abortion. To compare Amsel Criteria and Nugent Criteria for diagnosis of bacterial vaginosis. Methods: A cross sectional study involving 260 patients with preterm and term labour was conducted at a tertiary care hospital in North India. BV was determined to be present or absent on the basis of Amsel’s criteria and Nugent’s criteria. Pearson’s chi-square test was used to demonstrate the difference between both groups with respect to various categorical data. Results: Amsel’s criteria and Nugent’s criteria were reliable diagnostic methods. As compared to Nugent scoring system, Amsel’s criteria had sensitivity of 75%, specificity of 95%, positive predictive value of 90% and negative predictive value of 86%. Conclusions: Although the Amsel’s criteria is a convenient and inexpensive method of diagnosing bacterial vaginosis, it is not always reliable. Nugent’s criteria is considered as a gold standard for the diagnosis of bacterial vaginosis but it requires an experienced slide reader and considerable time and skill. If lab equipment is not available as in many developing countries, the diagnosis of BV can be simplified by using a combination of any two Amsel’s criteria like vaginal pH and whiff test which had highest sensitivity and specificity (90.19% and 97.78%) respectively as seen in present study.